Development of Tourism Villages Based on Local Wisdom to Improve the Economy of Local Communities - Sa'ban, L.M. Azhar; Sadat, Anwar; Wijaya, Andy Arya Maulana; Amiruddin, Amirudin (Jurnal Studi Ilmu Pemerintahan, 2024)
This research aims to identify the potential and challenges in developing a local wisdom-based tourism village in Sombano Village, Wakatobi Regency. The village is rich in natural resources such as beaches, lakes, and mangrove forests that have begun to be converted into tourist attractions. This research used a descriptive method with a qualitative approach, where data was collected through observation, interviews, and documentation. The research findings show that Sombano Village has great potential to become an attractive rural tourism destination, supported by distinctive social and cultural life and stunning natural beauty. The development of this tourism village is expected to be carried out by considering the socio-cultural characteristics of the local community to ensure sustainability and acceptance by the community. Some aspects of local wisdom that support the development of tourist villages in Sombano include tourist attractions, accessibility, tourist facilities, community empowerment, and marketing and promotion. However, of the five aspects, only three have been running well: tourist attraction, accessibility, and community empowerment. The other two aspects, tourist facilities, and marketing, still face significant challenges. The implications of these findings emphasize the importance of government intervention and investment in infrastructure development and marketing strategies to optimize tourism potential in Sombano Village. The limitations of this study include limitations in the generalizability of the findings due to its focus on a single village, as well as the use of qualitative methods that do not allow for quantitative measurement of economic impacts. Further research is recommended to expand the geographical coverage and use a more diverse approach.